The Role of Learning-oriented Language Assessment in Promoting Interactional Metadiscourse in Ectenic and Synoptic EFL Learners - Rajab Esfandiari; Omid Allaf-Akbary (Journal of Modern Research in English Language Studies)
In recent decades, undivided attention has been drawn to the examination of metadiscourse in different contexts, genres, languages, and disciplines. Nevertheless, a large body of research has been predominantly centred on the qualitative examination of potential metadiscourse markers and their associated functions. In the current study, we drew on an embedded design and followed learning-oriented language assessment (LOLA) in the use of interactional metadiscourse markers (IMMs) to better understand metadiscourse use by ectenic (n = 27) and synoptic (n = 30) learners using integrative writing tasks. To that end, 57 intermediate language learners completed Ehrman and Leaver’s (2003) learning style questionnaire. We followed Hyland’s (2019) interpersonal metadiscourse markers to determine the learners’ realisation of metadiscourse in their writing. SPSS (version 25) was run to analyse the quantitative data, and MAXQDA (version 2020) the think-aloud data. The results of chi-square analyses showed that ectenic learners outperformed synoptic ones following LOLA in the employment of IMMs. The results of inductive thematic analyses revealed that synoptic learners benefitted from the utilization of LOLA in employing IMMs in their integrative writing tasks. The findings suggest that the use of LOLA as a pedagogical method can effectively develop the writing proficiency of EFL learners.